Structures and absolute configurations of phomalones from the coral-associated fungus Parengyodontium album sp. SCSIO 40430. Issue 27 (29th June 2021) - Wang, Lu; Huang, Yanbing; Zhang, Liping; Liu, Zhiwen; Liu, Wei; Xu, Huixin; Zhang, Qingbo; Zhang, Haibo; Yan, Yan; Liu, Zhiyong; Zhang, Tianyu; Zhang, Wenjun; et al.
Abstract : Coral-associated microorganisms are likely to play an important role in host defense by the production of antimicrobials, such as enantiomeric mixture of phomalones. Abstract : Coral-associated microorganisms are likely to play an important role in host defense by the production of antimicrobials. Six new chromanones, namely, phomalichenones H-M (5, 6, and 8–11 ), and ten known analogues (1–4, 7, and 12–16 ) were isolated from the coral-associated fungus Parengyodontium album sp. SCSIO 40430. Their structures were elucidated by comprehensive spectroscopic analyses. In addition, the structure of 8 was confirmed by X-ray crystallographic analysis. Resolution using a chiral column showed that each of the compounds 1–8 was an enantiomeric mixture with variable enantiomeric excess (ee) values. Their absolute configurations were determined by a comparison of the experimental and calculated ECD data and by a modified Mosher's method. A plausible biosynthetic scheme was proposed for the production of 1–16 . Compounds 2, 3, 13, and 14 were found to be active against Mycobacterium tuberculosis H37Ra with MIC values of 16–64 μg mL −1 .